Synergetic tuning of electrical/thermal transport via dual‐doping in Bi0.96−xMgxPb0.06CuSeO. Issue 4 (22nd November 2018) - Liu, Yong; Zhu, Yingcai; Liu, Wei‐Shu; Marcelli, Augusto; Xu, Wei
Abstract: The layered oxyselenides BiCuSeO was recently discovered as potential thermoelectric. Our result reveals that the substitute for atom Bi 3+ by Pb 2+ & Mg 2+ in (Bi2 O2 ) 2− play an important role in electrical transport properties. The maximum electrical conductivity obtained is 460 Scm −1 for Bi0.84 Mg0.10 Pb0.06 CuSeO at RT, highly above the 15 Sm −1 for BiCuSeO. In synergy with low thermal conductivity (0.6‐0.4 Wm −1  K −1 ) and large thermopower (300‐500 μVK −1 ), the highest ZT is achieved about 0.80 at 873 K for Bi0.88 Mg0.06 Pb0.06 CuSeO.